МЕЖДИСЦИПЛИНАРНЫЙ ПОДХОД К СОПРОВОЖДЕНИЮ РЕБЕНКА С ОГРАНИЧЕННЫМИ ВОЗМОЖНОСТЯМИ ЗДОРОВЬЯ В ДОШКОЛЬНОЙ ОБРАЗОВАТЕЛЬНОЙ ОРГАНИЗАЦИИ - Бекманова, Ж.А. (SCIENCE and SOCIETY, 2025)
The article examines the interdisciplinary approach as a foundation for organizing comprehensive psychological and pedagogical support for children with disabilities (special educational needs) in preschool education settings. It substantiates the necessity of team collaboration among professionals from different fields - educators, psychologists, speech therapists, special education teachers, and medical personnel - as well as the active involvement of parents in supporting the child. Current scientific data confirming the effectiveness of this approach in the context of inclusive practice are presented. The article analyzes structural and organizational aspects of specialist collaboration, identifies barriers, and suggests ways to overcome them. The conclusion emphasizes the need for systematic training of personnel for interdisciplinary support within preschool educational institutions.